Do Domestic Investors with the Smallest Trading Orders Use Momentum Strategies in The IDX? - Syamni, Ghazali; Wardhiah, Wardhiah; Abd Majid, M. Shabri; Faisal, Faisal; Musnadi, Said (Universitas Prasetiya Mulya, 2021)
This study aims to examine the use of the momentum strategy of domestic investors who trade small order sizes on IDX. The data used in this study is intraday trade transaction data from the LQ 45 Index for March, April and May 2017 obtained from The Indonesia Capital Market Institute. The method of data analysis used is the market-adjusted model approach. The results of this study indicate that domestic investors who trade in small order sizes tend to use the momentum strategy in government and non-government stock issuers. This finding implies that when IDX is in a good performance, investors should take advantage of this condition because buying stocks that have already been performing well provides a significant short-term abnormal return.Â https://doi.org/10.21632/irjbs.14.1.35-47